Skrining kandungan metabolit sekunder ekstrak daun lamtoro (leucaena leucocephala) secara kualitatif dan kuantitatif menggunakan spektrofotometer uv-vis - A'yun, Ziskino Qurota (Maliki Interdisciplinary Journal, 2025)
Lamtoro (Leucaena leucocephala) is a plant with potential in pharmacology because it contains several potential secondary metabolites. This study was conducted to identify the secondary metabolite content and calculate the total phenol content of lamtoro leaf extract. The methods used in this study were qualitative tests with phytochemical screening using color reactions to identify secondary metabolite compounds and quantitative methods using a UV-Vis spectrophotometer to test the total phenol content of the extract. The results of the qualitative test of secondary metabolites in lamtoro leaf extract successfully identified the presence of alkaloids, flavonoids, phenols/tannins, triterpenoids, and saponins. The quantitative test of phenol content showed that this extract had a total phenol content of 84.5723 mg GAE/g in 10.51 mg of sample reacted using Folin-Ciocalteu reagent an . This phenol content can be categorized as high phenol content, so it has the potential to be developed in the pharmaceutical field, one of which is as an alternative antioxidant.